2006
DOI: 10.1073/pnas.0605858103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating alternative hypotheses for the early evolution and diversification of ants

Abstract: Ants are the world's most diverse and ecologically dominant eusocial organisms. Resolving the phylogeny and timescale for major ant lineages is vital to understanding how they achieved this success. Morphological, molecular, and paleontological studies, however, have presented conflicting views on early ant evolution. To address these issues, we generated the largest ant molecular phylogenetic data set published to date, containing Ϸ6 kb of DNA sequence from 162 species representing all 20 ant subfamilies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

55
658
8
21

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 458 publications
(742 citation statements)
references
References 51 publications
55
658
8
21
Order By: Relevance
“…In order to evaluate whether different approaches give Figure 1 Ant species used in this study. The divergence estimates are in My and based on large-scale sequence data from Brady et al (2006) and Moreau et al (2006). CSP evolution in ants J Kulmuni et al similar results, we made a neighbour-joining tree of each alignment and confirmed that different alignment methods produced similar overall topology.…”
Section: Sequence Alignment and Analysissupporting
confidence: 50%
“…In order to evaluate whether different approaches give Figure 1 Ant species used in this study. The divergence estimates are in My and based on large-scale sequence data from Brady et al (2006) and Moreau et al (2006). CSP evolution in ants J Kulmuni et al similar results, we made a neighbour-joining tree of each alignment and confirmed that different alignment methods produced similar overall topology.…”
Section: Sequence Alignment and Analysissupporting
confidence: 50%
“…The basal rooting of present-day Martialinae and Leptanillinae places the origin and early diversification of ants as far back as Early Cretaceous times. Molecular phylogenetic studies of these and other living species place the origin of almost all the living subfamilies in the early or middle Late Cretaceous or the Early Paleogene Periods (29)(30)(31). The history of the ants as a whole, however, appears not to extend as far back as the Jurassic Period (29)(30)(31).…”
Section: Monogamy and Origin Of Eusocialitymentioning
confidence: 99%
“…The origin of eusociality in halictid bees occurred during the mid-Paleogene Period, 35 Mya (27,28). The ants appeared, evidently from a single aculeate wasp ancestor (29), during the Cretaceous Period, about 140 Mya (29)(30)(31). By the Paleogene Period and likely during the very Late Cretaceous, most or all of the contemporary 21 ant subfamilies had separated (29-31).…”
Section: The Geological Origins Of Eusocialitymentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the course of their 115-168 million year history (7,8), these diverse and ecologically dominant insects have repeatedly evolved symbiotic relationships with sap-feeding insects (9), plants (10), and microbes (11, 12, 13), including nitrogen-recycling and upgrading Blochmannia species harbored by ants from the Camponotini (carpenter ants) (14, 15). With only a few exceptions outside of this group (16)(17)(18)(19)(20) and the tribe Attini (13), we know little about the identities and significance of bacteria across Ͼ12,000 described ant species.…”
mentioning
confidence: 99%